ANALISIS SOSIAL EKONOMI MASYARAKAT TERHADAP KEBERADAAN PABRIK KELAPA SAWIT PT. BUKIT SAWIT SEMESTA - wisesty soulina; Widya Prarikeslan (JURNAL BUANA, 2023)
Development in plantation-based agriculture play an importants roles in the national economyc. Development of agriculture in the field of plantations can improve the welfare of life. Palm oil is one of the leading plantations commodities in Indonesia. Plants with palm oil and palm kernel oil products have high economic value and are a major contributor to the country's foreign exchange. This research is a descriptive research with a quantitative approach. This study does not test hypotheses, but is only limited to describing or describing information as it is in accordance with the variables studied. Results showed that there were changes in people's lives in the aspects of work, income, social interaction and public facilities around PT. Bukit Sawit Semesta both before and after the establishment of the company. Based on the research results it can be concluded that the establishment of PT. Bukit Sawit Semesta has an impact related to the social and economic conditions of the community around the company.